National fantasy, impossible gaze: the Kurdish question in popular Turkish cinema - AYDINLIK, YASİN (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
This essay explores representations of the Kurdish question in the new popular films of Turkey including Eskiya/The Bandit, Vizontele, Deli Yurek: Bumerang Cehennemi/Wildheart: Hell of Boomerang, Kurtlar Vadisi: Iraq/Valley of the Wolves: Iraq, Gunesi Gordum/I Saw the Sun, Nefes/The Breath and Mucize/The Miracle. I use the notion of ideological fantasy to explain how filmic reality is constructed within these films. I argue that popular films of new Turkish cinema addressing the Kurdish question are national fantasies reconstituting the social, historical and political realities of the problem in accordance with the changing state discourse.
Keywords: new Turkish cinema; popular Turkish cinema; national cinema; national gaze; ideological fantasy; Kurdish question; RESISTANCE